Technical Guidance on Homestay Management in the Field of Housing Arrangements in Girikerto Village, Ngawi Regency, East Java Province - Prastowo, Ichwan (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2024)
The implementation of this community service aims to provide technical guidance in managing Homestays in the field of housing arrangements in the tourist village of Girikerto, N,gawi Regency, East Java Province. Technical guidance is provided with the goal of fostering, developing, and advancing homestays by imparting knowledge and skills to managers and relevant institutions to create professional homestay human resources. The method of technical guidance involves theory and practice tailored to the conditions of homestays. The outcomes for participants in this technical guidance include obtaining a job description and standard operating procedures as work guidelines, acquiring skills in housing arrangements, and being able to apply all the knowledge gained in running homestay operations.